The prevalence, diagnostic accuracy and genotype-phenotype correlation of GNAS mutations in fibrous dysplasia: a meta-analysis - Zhang, Ao-Bo; Zhang, Jian-Yun; Xue, Jiang; Wu, Zhen-Chao; Xu, Zhi-Xiu; Sun, Li-Sha; Li, Tie-Jun (Frontiers in Genetics, 2024)
Background There is inconsistent evidence regarding the accuracy of GNAS mutations identification for the diagnosis of FD/MAS. This study was performed to estimate the prevalence and diagnostic accuracy of GNAS mutations detection and to preliminarily investigate the genotype-phenotype correlation in FD patients. Methods Five electronic databases were searched from 1995 to 2024 using search terms related to GNAS and fibrous dysplasia. Observational studies of FD patients undergoing GNAS mutation detection in FD were included. Results A total of 878 FD patients were included. The pooled prevalence of GNAS mutations in FD based on the random effects model was 74% (95% CI = 64%–83%). Regarding diagnostic accuracy, a sensitivity of 0.83 (95% CI, 0.65–0.96), specificity of 0.99 (95% CI, 0.98–1.00) and the area under the receiver operating characteristic curve of 98.38% were found. Additionally, meta-analysis and Fisher’s test showed the GNAS mutation types were significantly associated with FD types (OR = 3.51, 95% CI = 1.05 to 11.72; p < 0.05). Conclusion A high detection rate of GNAS mutations occurred in FD, and its detection is reliable for diagnosing FD. Additionally, GNAS mutation type was types were significantly associated with FD type. Systematic Review Registration Identifier CRD42024553469.